Chironomid Spatial Distribution within the upstream of Sungai Langat Catchment - Ahmad, A.K.; Abd. Aziz, Z.; Shuhaimi-Othman, M. (Universiti Kebangsaan Malaysia, 2014)
A study on the chironomids (Diptera:Chironomidae) diversity at pristine ecosystem was carried out at upstream of Sungai Langat, Selangor. The study determines chironomids distribution and composition at 7 streams and river within the upstream site of Langat Catchment. Chironomid was sampled using Surber net and water quality was measured based on Malaysia WQI. The result indicated that Chironomidae was represented by three subfamilies namely Chironominae, Orthocladiinae and Tanypodinae, which comprises of 2502 individuals. Chironominae was the most dominant subfamily (1619 individuals) followed by Orthocladinae (629 individuals) and Tanypodinae (254 individuals). Polypedilum (subfamily: Chironominae) is the most dominant genus found followed by Rheocricotopus (subfamily: Orthocladiinae), Microtendipes and Cryptochironomus. Polypedilum was abundant in all stations except Sg. Langat 3 which was dominated by Rheocricotopus. Sungai Langat 3 has the highest number of individual (1113) which is (44.5%) from total chironomid individuals and followed by Sg. Lolo with 468 individual that were dominated by Polypedilum.